2022
DOI: 10.1021/acs.nanolett.2c02144
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose-Based Cryogel Microspheres with Nanoporous and Controllable Wrinkled Morphologies for Rapid Hemostasis

Abstract: First-aid hemostatic agents for acute bleeding can save lives in emergency situations. However, rapid hemostasis remains challenging when uncontrolled hemorrhage occurs on lethal noncompressible and irregular wounds. Herein, cellulosebased cryogel microspheres with deliberately customized micromorphologies for ultrafast water transportation and diffusion, including the shark skin riblet-inspired wrinkled surface with low fluid drag and the hydrophilic nanoporous 3D networks, are developed to deal with the acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 47 publications
(60 reference statements)
0
22
0
Order By: Relevance
“…Hydrogel adhesives have attracted great interest as promising alternatives to surgical sutures and staples for biomedical applications such as rapid hemostasis, wound sealing, and medical device fixation. However, achieving rapid and strong underwater adhesion is very challenging owing to the presence of hydration layers on the hydrogel surfaces upon their exposure to aqueous environments. This hydration layer severely prevents the in situ hydrogel formation and direct contact between hydrogels and substrates, causing the adhesion failure at target sites. For instance, cyanoacrylate adhesives solidify immediately to form rigid plastics when encountering body fluids, which cannot accommodate the movement of dynamic tissue surfaces. Fibrin-based adhesives contain a large amount of highly hydrated networks, causing mechanically much weaker than biological tissues. Thus, the development of novel adhesive hydrogels with rapid in situ gelation and sufficient underwater adhesion performance remains imperative for wound closure and hemostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogel adhesives have attracted great interest as promising alternatives to surgical sutures and staples for biomedical applications such as rapid hemostasis, wound sealing, and medical device fixation. However, achieving rapid and strong underwater adhesion is very challenging owing to the presence of hydration layers on the hydrogel surfaces upon their exposure to aqueous environments. This hydration layer severely prevents the in situ hydrogel formation and direct contact between hydrogels and substrates, causing the adhesion failure at target sites. For instance, cyanoacrylate adhesives solidify immediately to form rigid plastics when encountering body fluids, which cannot accommodate the movement of dynamic tissue surfaces. Fibrin-based adhesives contain a large amount of highly hydrated networks, causing mechanically much weaker than biological tissues. Thus, the development of novel adhesive hydrogels with rapid in situ gelation and sufficient underwater adhesion performance remains imperative for wound closure and hemostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Some biopolymer-based powders, such as Celox® and NexStat®, have been introduced into military and civilian settings. In recent years, there have been many advanced designs for hemostatic powders with respect to structural regulation and functionalization [ 154 , 155 ].…”
Section: Form Design Of Hemostasis Materialsmentioning
confidence: 99%
“…Such cryogels are reported to absorb blood within seconds. Zhan et al reported the fabrication of cellulose@polydopamine/Thymol (Tm/ Cell@PDA) cryogel microspheres (400 ± 15 μm) with shark skin riblet-inspired wrinkled surface to prevent acute bleeding within 10 seconds of application [ 122 ] . The fabricated cellulose microsphere could absorb blood six times its weight.…”
Section: Hydrogels and Cryogels As Hemostatsmentioning
confidence: 99%